Drop coating deposition of a liposome suspension on surfaces with different wettabilities: "coffee ring" formation and suspension preconcentration - Kočišová, Eva; Petr, Martin; Šípová, Hana; Kylián, Ondřej; Procházka, Marek (Physical chemistry chemical physics, 2016)
Evaporation of a drop of biomolecular solution on a solid surface typically creates a ring-shaped drying pattern, formed by the so-called "coffee ring" effect. The size and shape of the "coffee ring" pattern is strongly dependent on the properties of the surface as well as on the deposited molecular solution or suspension. In this paper, we tested six types of surfaces differing in their physico-chemical surface characteristics (contact angles, wettability and roughness) as well as in the presence or absence of a base metal layer. The tested surfaces include two fluorocarbon coated metallic surfaces (commercial SpectRIM™ from Tienta Sciences, Inc. based on a smoothed stainless steel and non-commercial aluminium surface), three silanized glass surfaces and polished CaF2. The results showed that the formation of a "coffee ring" was influenced by surface wettability as well as by lipid concentration in the drop. Drop coating deposition Raman (DCDR) spectroscopy was used to compare the ability of the tested surfaces to preconcentrate molecules in the ring and therefore improve detection sensitivity. It was shown that surfaces with a contact angle of 90° and higher produce smaller drying patterns than more hydrophilic surfaces. In these drying patterns, the model liposomes were more efficiently preconcentrated, which resulted in a higher Raman signal of the liposomes. The applicability of surfaces with static contact angles less than 90°, high water contact angle hysteresis and no metal layer (silanized glass, CaF2) is limited to samples with high liposome concentrations.